(untitled) (Emancipação, 2024)
The continuous wandering of nomads and wanderers permeates from personal, social and structural problems influenced by capitalism, globalization and modernity. Social ills, physical and psychological suffering, alcohol consumption and the absence of the State are striking. Tried to identify the characteristics of wandering and nomadism; presenting, as an experience report, statistical data and main moments of the Lives on the Road Project: wanderers and walkers. Using bibliographic review and field work, data of the approaches taken in the project were presented. Content Analysis (Bardin, 2016) was used to process the information. It was verified, with a significant sample, convictions that already exist in the academic environment and unpublished data in the scientific literature on contemporary wandering and nomadism were presented. Condition borne by road wanderers and walkers is the last alternative of a life permeated by suffering and disappointment, where material and existential misery is manifested, projecting a low life expectancy for the walker.